THE ABILITY OF WRITING NEWS ITEM TEXT USING THE TEAM GAME TOURNAMENT LEARNING MODEL ON 8TH GRADE STUDENTS - Dolly Apriani Makasombo; Susan Monoarfa; Intama Jemy Polii (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims to evaluate the ability to write news item texts of 8th grade students using the Team Game Tournament learning model. This descriptive qualitative research was conducted at SMP Katolik Don Bosco Bitung. The data sources were 25 8th grade students at SMP Katolik Don Bosco Bitung. Data collection was done through written test, especially news text writing test. The results of the study were grouped into four assessment categories: excellent, good, fair, and poor. Data analysis revealed that 15 students (60%) showed the level of news text writing skills in the excellent category, 6 students (24%) in the good category, 4 students (16%) in the fair category, and no students were in the less category. The conclusion of this study is that the news text writing skills of the 8th grade students at SMP Katolik Don Bosco Bitung can generally be categorized as good, with an average score of 84.2 on a scale range of 0-100.